Optimizing Molecular Diagnostics for Huntington's Disease and Hemochromatosis - Hurtado Alindes, Ana (2022)
The molecular characterization of the mutations causing hereditary diseases are important tools for diagnosis, prognosis and eventually treatment. Huntington's disease is a neurodegenerative disease producing spastic uncontrolled movements and is caused by the expansion of a trinucleotide (CAG)n within the first exon of the gene HD located at 4p16. Hemocromatosis is a liver disease causing cirrosis, diabetes and heart problems, in addition one third of patients dies of hepatocarcinoma. Almost all cases of hemocromatosis are due to mutations in the gene HFE at 6p21, being C282Y and H63D the mutations most frequently detected in Europe and USA. We are establishing the molecular diagnosis of different diseases starting with Huntington disease and hemochromatosis as the begining of a service to the Peruvian comunity.